PENGARUH FAKTOR GEOGRAFIS, DEMOGRAFIS DAN PSIKOGRAFIS PADA PEMASARAN REALESTAT BERKONSEP MINIMALIS DI SURABAYA - Sofia Hendrastuti; Christiono Utomo (Lembaga Penelitian dan Pengabdian kepada Masyarakat- Institut Teknologi Sepuluh Nopember, 2006)
In the beginning of 2005, property business in Surabaya went into a new decade by the emergence of the new set of trend in housing/real estate, which is often called as 'minimalist architecture'. Thosewho apply the system of multi-concepts, would have no difficulties in marketing their products. To those developed minimalist architectures showed that developers chose the system of single-concept could not fulfill their targets of marketing. Thus we could consider this as an indicator of certain formula, that is: what kind of factors that would be considered by customers-to-be before buying 'minimalist-housing'? and how was the character of those costumers- to-be in its relations with geographic, demographic, and psychographic aspects?. The sampling techniques used